Hydroxychloroquine‐induced acute generalized exanthematous pustulosis: a series of seven patients and review of the literature. (17th February 2021) - Chaabouni, Rim; Bahloul, Emna; Ennouri, Mariam; Atheymen, Rim; Sellami, Khadija; Marrakchi, Slaheddine; Charfi, Slim; Boudaya, Sonia; Amouri, Meriem; Bougacha, Noura; Turki, Hamida
Abstract: Background: Hydroxychloroquine (HCQ)‐induced acute generalized exanthematous pustulosis (AGEP) is poorly described in the literature. The aim of our study was to characterize the clinical, laboratory, allergological, and genetic features of HCQ‐induced AGEP. Methods: We conducted a retrospective study of patients with HCQ‐induced AGEP diagnosed between 2011 and 2019. We performed molecular analysis to identify variations in the IL36RN gene. We also reviewed similar cases reported between 1991 and March 2020. Results: Seven female patients were included. The mean age was 47 years old, and the average time from HCQ start to onset of symptoms was 40 days. All patients received topical steroids with a full resolution of the rash within an average of 39 days after HCQ withdrawal. Patch tests were performed for three patients with positive results in one case. Genetic analyses were performed for three patients, and no mutation in the IL36RN gene was identified. Conclusion: The latent period and the duration for resolution of HCQ‐induced AGEP may be longer than with other drugs due to the metabolic characteristics of HCQ. Mutations in the IL36RN gene were not identified in our patients.